Peningkatan Pengetahuan Remaja Tentang Perkembangan Remaja Pada Masa Pubertas - Fauza, Rahmawani (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2025)
Puberty is a crucial phase in adolescent development, marked by physical, psychological, and social changes. Limited knowledge about puberty can lead to anxiety and risky behaviors. This study aimed to assess students' knowledge of puberty before and after receiving educational intervention and to evaluate its effectiveness. A pre-test and post-test design was applied to 24 eighth-grade students at SMP Imelda Medan using a structured questionnaire. Results showed that prior to the intervention, 45.8% of students had low knowledge levels. After receiving interactive education through visual media and group discussions, 81.5% of students demonstrated a good level of understanding. The findings indicate that appropriate health education methods can significantly improve adolescents’ understanding of puberty. It is recommended that reproductive health education be integrated into the school curriculum with the involvement of teachers, parents, and healthcare professionals to ensure comprehensive understanding.